The Application of Inventory Model in Material Planning Department atCompany of XYZ - Indah Saragiha, Nova; Decker Lumban Tobinga, Martin (International Journal of Psychosocial Rehabilitation, 2020)
Company XYZ is the first company in Indonesia to produce airplanes. Materials needed to produce the airplanes consist of metal, non-metal, and others. In the production process, there is a condition where materials of metals are not available or run out. The unavailable materials are then substituted with other materials of metals. The problem is that there are several substitute materials that are more expensive than the initial materials. On average, the difference or the price gap between the substituted materials and the initial materials is 105.78%. This gap shows that the company of XYZ needs to control their inventory more effectively. An inventory model is applied to the real system, which is the Material Planning Department, to decrease this gap. That inventory model is a simple probabilistic model. The result shows that the simple probabilistic model is able to decrease the gap to 32.81%.